Antiracism Education In and Out of Schools (Springer International Publishing, 2018)
This book explores how antiracism theories can be translated into practice within formal education, as well as in other educational programs outside schools, as very often racism occurs outside the school environment. Combating racism both in and out of school therefore increases the chances of overcoming issues of racism. As racism continues to plague the world, efforts to combat it deserve more attention and diversification across all walks of life. In education, such efforts benefit from being modeled within the framework of antiracism education, rather than simpler multicultural and intercultural theorization and understanding which have proved popular. As such, this book critiques integration and multicultural programs, and instead highlights the advantages of grounding such programs within an antiracist framework. This book demonstrates why and how antiracism education is key to challenging issues of racial injustice at a time when multiculturalism and interculturalism have being proclaimed "dead". It will be highly relevant to researchers and students working in the areas of Education and Sociology, particularly those with an interest in antiracism methodologies. .